2010
DOI: 10.1590/s0080-62342010000400029
|View full text |Cite
|
Sign up to set email alerts
|

Validação de indicadores da classificação dos resultados de enfermagem para pacientes com problemas ortopédicos

Abstract: Estudo de validação de conteúdo, descritivo, transversal, com abordagem quantitativa, realizado num hospital universitário. Objetivou-se validar os indicadores de quatro resultados de enfermagem da Classificação dos Resultados de Enfermagem - NOC, para o diagnóstico de enfermagem Déficit no autocuidado: banho/higiene, apresentados por pacientes em pós-operatório de cirurgia ortopédica. Construiu-se um instrumento contendo os indicadores dos resultados Autocuidado: Atividades da Vida Diária, Autocuidado: Banho,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
4
0
5
Order By: Relevance
“…It was noted that the indicators of the outcomes "Selfcare: Activities of Daily Living (ADL)", "Self-care: Bathing", "Self-care: Hygiene" and "Self-care: Oral Hygiene" allowed the monitoring of patients in relation to self-care (19) . A study conducted in 2012 identified the most appropriate nursing outcomes for specific goals documented in the medical records of previously hospitalized patients.…”
Section: Applicability Of Nursing Outcomes In Clinical Practicementioning
confidence: 99%
“…It was noted that the indicators of the outcomes "Selfcare: Activities of Daily Living (ADL)", "Self-care: Bathing", "Self-care: Hygiene" and "Self-care: Oral Hygiene" allowed the monitoring of patients in relation to self-care (19) . A study conducted in 2012 identified the most appropriate nursing outcomes for specific goals documented in the medical records of previously hospitalized patients.…”
Section: Applicability Of Nursing Outcomes In Clinical Practicementioning
confidence: 99%
“…Almeida et al 32 endeavored to validate four nursing outcomes' indicators of the Nursing Outcomes Classification presented by patients in postoperative of orthopedic surgery. An instrument containing the outcome indicators Self-care Activities of Daily Living, Bathing, Hygiene and Oral Hygiene was built, along with a Likert scale ranging from 1 to 5 (1 = not important, 5 = extremely important).…”
Section: General Reviewmentioning
confidence: 99%
“…Nacionalmente, desenvolveu-se um sistema de classificação de pacientes relacionado à identificação de diferentes graus de complexidade assistencial entre os clientes, almejando proporcionar informações para o processo de tomada de decisão quanto à alocação de recursos humanos, à monitorização da produtividade, aos custos da assistência de enfermagem, à organização dos serviços e ao planejamento da assistência de enfermagem. Porém, para isto não foi utilizada avaliação de resultados do paciente (25)(26) .…”
Section: Pr Pr Prunclassified
“…No Brasil, ainda é incipiente o uso de resultados de enfermagem de forma sistematizada e publicações em periódicos científicos são escassas, conforme mencionado anteriormente. Porém, pesquisa em andamento no Hospital de Clínicas de Porto Alegre, vinculada à Escola de Enfermagem da Universidade Federal do Rio Grande do Sul, vem estudando a possibilidade de implantação da Classificação dos Resultados de Enfermagem no sistema informatizado da instituição, sendo este um estudo pioneiro no país (26) .…”
Section: Pr Pr Prunclassified